Labeling of pancreatic islets with iron oxide nanoparticles for in vivo detection with magnetic resonance - Berkova, Zuzana; Jirak, Daniel; Zacharovova, Klara; Kriz, Jan; Lodererova, Alena; Girman, Peter; Koblas, Tomas; Dovolilova, Eva; Vancova, Marie; Hajek, Milan; Saudek, Frantisek (Transplantation, 2008)
In vitro labeling of pancreatic islets with iron nanoparticles enables their direct posttransplant visualization by magnetic resonance; however, there is still a discrepancy in the fate of iron nanoparticles. This study was performed to detail the labeling process, consequently to improve the labeling efficacy and to confirm safety for islet cells. The islets were visible on T2*-weighted magnetic resonance images as hypointense spots immediately after 1-hr cultivation. Although at this time already the sufficient superparamagnetic effect was achieved, most of the particles were deposed in islet macrophages and only later were they found in endosomes of endocrine islet cells. The iron content depended on length of culture period. The labeled islets showed an intact ultrastructure, responded normally to glucose stimulation in vitro, and were able to treat experimental diabetes. For purpose of subsequent magnetic resonance imaging, a 24-hr culture with ferucarbotran leads to sufficient labeling with no apparent adverse effect on beta cell morphology or function.
Keywords: železité sloučeniny; Ferric Compounds; magnetická rezonanční tomografie; Islets of Langerhans Transplantation; Langerhansovy ostrůvky; krysa rodu Rattus; Time Factors; kovové nanočástice; kultivované buňky; Animals; Metal Nanoparticles; barvení a značení; zvířata; beta-buňky; makrofágy; Rats; transplantace Langerhansových ostrůvků; časové faktory; Cells, Cultured; Insulin-Secreting Cells; Islets of Langerhans; Staining and Labeling; Magnetic Resonance Imaging; Macrophages